Donor KIR genotype based outcome prediction after allogeneic stem cell transplantation: no land in sight - Schetelig, Johannes; Baldauf, Henning; Heidenreich, Falk; Hoogenboom, Jorinde D.; Spellman, Stephen R.; Kulagin, Alexander; Schroeder, Thomas; Sengeloev, Henrik; Dreger, Peter; Forcade, Edouard; Vydra, Jan; Wagner-Drouet, Eva Maria; et al. (Frontiers in immunology, 2024)
Optimizing natural killer (NK) cell alloreactivity could further improve outcome after allogeneic hematopoietic cell transplantation (alloHCT). The donor’s Killer-cell Immunoglobulin-like Receptor (KIR) genotype may provide important information in this regard. In the past decade, different models have been proposed aiming at maximizing NK cell activation by activating KIR-ligand interactions or minimizing inhibitory KIR-ligand interactions. Alternative classifications intended predicting outcome after alloHCT by donor KIR-haplotypes. In the present study, we aimed at validating proposed models and exploring more classification approaches. To this end, we analyzed samples stored at the Collaborative Biobank from HLA-compatible unrelated stem cell donors who had donated for patients with acute myeloid leukemia (AML) or myelodysplastic neoplasm (MDS) and whose outcome data had been reported to EBMT or CIBMTR. The donor KIR genotype was determined by high resolution amplicon-based next generation sequencing. We analyzed data from 5,017 transplants. The median patient age at alloHCT was 56 years. Patients were transplanted for AML between 2013 and 2018. Donor-recipient pairs were matched for HLA-A, -B, -C, -DRB1, and -DQB1 (79%) or had single HLA mismatches. Myeloablative conditioning was given to 56% of patients. Fifty-two percent of patients received anti-thymocyte-globulin-based graft-versus-host disease prophylaxis, 32% calcineurin-inhibitor-based prophylaxis, and 7% post-transplant cyclophosphamide-based prophylaxis. We tested several previously reported classifications in multivariable regression analyses but could not confirm outcome associations. Exploratory analyses in 1,939 patients (39%) who were transplanted from donors with homozygous centromeric (cen) or telomeric (tel) A or B motifs, showed that the donor cen B/B-tel A/A diplotype was associated with a trend to better event-free survival (HR 0.84, p=.08) and reduced risk of non-relapse mortality (NRM) (HR 0.65, p=.01). When we further dissected the contribution of B subtypes, we found that only the cen B01/B01-telA/A diplotype was associated with a reduced risk of relapse (HR 0.40, p=.04) while all subtype combinations contributed to a reduced risk of NRM. This exploratory finding has to be validated in an independent data set. In summary, the existing body of evidence is not (yet) consistent enough to recommend use of donor KIR genotype information for donor selection in routine clinical practice.